Cellulose dissolved in ionic liquids for modification of the shape of keratin fibers - Liu, Yuwei (2021)
The methylimidazolium chloride ionic liquid (IL) was successfully used for the dissolution of cotton cellulose. IL and IL-cellulose were investigated by X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectroscopy analyses. The obtained IL-cellulose was applied to wool and hair keratin fiber surfaces, forming a fine coating layer. From FT-IR and XRD analyses, the results suggested the reduction of hydrogen bonds and crystallinity in IL-cellulose-coated wool fibers. This effect was caused by covering the wool with the IL-cellulose coating, and good intrinsic mechanical properties were observed. Moreover, the dimensional performance of coated keratin fibers presented length variations of around 8 and 12% under wet and dry conditions for wool and hair fibers, respectively. Coated keratin fibers could be of great value for a cleaner process in the cosmetic area associated with their ability to stretch and curl when triggered by humidity.